Utilizing glycosylated hemoglobin to assess the clinical value of intracranial artery stenosis severity - Li, Xingyao; Fei, Aihua (Frontiers in Endocrinology, 2025)
PurposeThe aim of this study was to investigate the effect of glycosylated hemoglobin (HbA1c) on the severity of intracranial atherosclerotic stenosis (ICAS).Patients and methodsWe conducted a retrospective analysis of the clinical data of patients who underwent intracranial digital subtraction angiography (DSA) and were admitted to Xinhua Hospital, Shanghai Jiao Tong University, between December 2021 and April 2023. Collected information included age, gender, blood lipid levels, and smoking status. Patients were stratified into two groups based on HbA1c levels: elevated HbA1c (≥6.5%) and normal HbA1c (<6.5%). With DSA, ICAS was classified into anterior and posterior circulation subgroups according to vascular anatomy. Stenosis severity was graded with the Warfarin-Aspirin Symptomatic Intracranial Disease (WASID) trial criteria: no/mild stenosis (0%–49%), moderate stenosis (50%–69%), severe stenosis (70%–99%), and complete occlusion (100%). An ordinal multinomial regression analysis was employed to assess the association between HbA1c levels and ICAS severity.ResultsA total of 360 participants were included in this study. The severity of ICAS worsened with higher HbA1c levels. Further subgroup analysis revealed that HbA1c levels ≥6.5% were significantly and positively associated with anterior circulation stenosis (r=0.13, P=0.03) and showed a positive trend with posterior circulation stenosis (r=0.13, P=0.06). After adjusting for gender, age, and smoking status, higher HbA1c levels were linked to an increased severity of stenosis in both the anterior and posterior circulation. Among blood lipid parameters, triglyceride levels demonstrated a significant correlation with ICAS severity (P < 0.05). Furthermore, subgroup analyses revealed that age over 68 years with HbA1c elevation was a risk factor for anterior circulation ICAS (OR 2.04, 95% CI 1.11–3.81, P < 0.05), whereas age 68 years or under was a risk factor for posterior circulation ICAS (OR 2.12, 95% CI 1.16–3.97, P < 0.05).ConclusionThe severity of ICAS was positively associated with an elevated HbA1c level (≥6.5%). The association was more pronounced in the posterior circulation. Elevated triglyceride levels and age were also associated with ICAS progression.